Correlating Cathode/Electrolyte Interface Characteristics to SOFC Performance. (3rd May 2017) - Szász, Julian; Wankmüller, Florian; Joos, Jochen; Wilde, Virginia; Störmer, Heike; Gerthsen, Dagmar; Ivers-Tiffée, Ellen
Abstract : High-performance solid oxide fuel cells (SOFC) mostly utilize mixed conducting La1-x Srx Co1-y Fey O3- δ (LSCF) cathodes. The drawback with LSCF is the formation of non-conducting secondary phases (SrZrO3 ) when it is applied on Y2 O3 stabilized ZrO2 (YSZ) electrolytes. This secondary phase reaction can be prevented by applying a dense Gd-doped Ceria (GDC) between LSCF and YSZ. In this study, the characteristics of LSCF/GDC/YSZ interfaces were systematically modified by a variation in GDC sintering temperature. Our findings confirm a heterogeneous cathode/electrolyte interface composed of primary (LSCF, GDC and YSZ) and secondary phases (SrZrO3 and GDC-YSZ interdiffusion). The performance depends strongly on GDC sintering temperature and interface resistances can lead to performance reduction by ~2000% (1582 to 77mW∙cm 2 at 800 °C were measured). Regarding technical relevant processes, secondary phases appear and overshadow high-performing electrode properties. A deeper understanding of the interplay between chemical composition, processing and microstructure is provided to improve individual cell concepts.